2005
DOI: 10.1007/11520184_12
|View full text |Cite
|
Sign up to set email alerts
|

Semantic-Based Policy Engineering for Autonomic Systems

Abstract: Abstract. This paper presents some important directions in the use of ontologybased semantics in achieving the vision of Autonomic Communications. We examine the requirements of Autonomic Communication with a focus on the demanding needs of ubiquitous computing environments, with an emphasis on the requirements shared with Autonomic Computing. We observe that ontologies provide a strong mechanism for addressing the heterogeneity in user task requirements, managed resources, services and context. We then presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
10
0
4
Order By: Relevance
“…They argued that consistency maintenance for policies across domains is required when several domain ontologies are merged together and policies are being created on entities within these domains. Lewis et al [15] proposed a method to support policy engineering by using ontology-based semantic models of the managed system to enable automated reasoning about the resolution and interactions of policies.…”
Section: Enhancementmentioning
confidence: 99%
“…They argued that consistency maintenance for policies across domains is required when several domain ontologies are merged together and policies are being created on entities within these domains. Lewis et al [15] proposed a method to support policy engineering by using ontology-based semantic models of the managed system to enable automated reasoning about the resolution and interactions of policies.…”
Section: Enhancementmentioning
confidence: 99%
“…The advantages of semantic policy frameworks are analysed in [10], stating that semantic approaches using RDF/OWL as standards for policy representation enable runtime extensibility and adaptability of the system, as well as the ability to work with policies relating to entities described at different levels of abstraction. The use of ontology-based PBM to provide dynamically adaptive network management solutions is also proposed in [11].…”
Section: Semantic Managementmentioning
confidence: 99%
“…Also, it is not restricted to service oriented architectures as in [11], in which behaviour defined for a certain HL service affects the behaviour of the LL services in which the former is decomposed. It also presents the semantic web advantages for network management about working with data distributed over different systems with heterogeneous RDF-based semantics [11].…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Translating HLP into LLP is called policy refinement. There is no generic solution for policy refinement, but recent research results have shown that Semantic Web technology may be the first toolkit to solve this problem [1,5,2].…”
Section: Introductionmentioning
confidence: 99%